Cultural Views Inclusive in E-learning Risk Analysis - Alwi, NHM; Fan, IS (IEEE, 2024)
This paper presents an attempt to explore the relevance of stakeholder cultural views towards e-learning information security. An anthropological framework based on the Grid and Group Cultural Theory (CT) of Mary Douglas was used to classify the cultural view of each stakeholder groups in e-learning organisations. The CT framework identifies four cultural views - hierarchism, egalitarianism, individualism and fatalism. An approach based on Failure Mode and Effect Analysis (FMEA) was used to conduct a threat and risk analysis taking into account the four possible cultural views of each stakeholder role. This study focused on unintentional threats by human errors as these are easy to commit and difficult to control. For each stakeholder group, a critical threats list was generated highlighting the cultural views most exposed to threats. The findings indicate that cultural views have a significant influence on the susceptibility of the stakeholders to unintentional threats. This study suggests that cultural view of stakeholders should be considered in preparing the e-learning information security strategy.